(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article is devoted to the topic of effective use of software tools in the teaching of geometry, it contains ideas about the effect of using the GeoGebra program on the improvement of students’ mastery, and its advantage in describing geometric shapes.